Contact radiotherapy boost in association with 'watch and wait' for rectal cancer: initial experience and outcomes from a shared programme between a district general hospital network and a regional oncology centre. (September 2016) - Smith, F. M.; Al‐Amin, A.; Wright, A.; Berry, J.; Nicoll, J. J.; Sun Myint, A.
Abstract: Aim: Recent data have highlighted the potential of more intensive neoadjuvant protocols to increase and sustain the rate of complete response in rectal cancer managed nonoperatively. This study aimed to review the outcome of all patients from our district general hospitals network who had received standard neoadjuvant therapy and were additionally referred to a centre of excellence for contact X‐ray brachytherapy or high‐dose‐rate brachytherapy boost. Method: A retrospective, chart‐based review of all patients co‐managed in this manner was performed. Patient details were retrieved from a prospectively maintained departmental database. Indications for treatment, patient outcome and serial data from follow‐up clinical and radiological assessment were analysed. Results: Seventeen patients treated over a 6‐year period were identified. Median follow‐up was 20 (5–54) months. Fourteen patients were clinically staged as T2 or T3 and eight were clinically node positive. Three patients died, of whom only one was initially a surgical candidate but refused an exenteration. Of the 14 patients who remain alive, 11 (79%) have a sustained complete ( n  =   8) or partial ( n  =   3) response. Two patients had an incomplete response, one is being palliated and the other awaits salvage surgery. One patient underwent abdominoperineal excision for suspected local recurrence. Currently 13 (93%) surviving patients are stoma free. Conclusions: This series shows that the addition of a radiotherapy boost offered sustained responses and stoma‐free survival even in advanced disease and adverse patient populations whilst providing the majority of care closer to home.